Electrochemical Analysis of a System Based on W and Ni Combined with CeO2 as Potential Sulfur‐tolerant SOFC Anode. Issue 3 (22nd April 2016) - Escudero, M. J.; Fuerte, A.
Abstract: A formulation of tungsten and nickel combined with CeO2 (WNi‐Ce) was prepared and evaluated as sulfur‐tolerant anode for SOFC at intermediate temperature. Structural and morphological changes that take place in the system upon interactions with hydrogen sulfide were analyzed. The electrochemical performance was tested in a single cell, WNi‐Ce/LDC/LSGM/LSFC, varying H2 S concentration (0–500 ppm) at 750 °C using I–V curves, impedance spectroscopy and load demands. The highest cell performance was reached in H2 and decrease with H2 S content increase in the fuel from 226 mW cm −2 in pure H2 to 108 mW cm −2 in 500 ppm H2 S/H2 . Essentially, no decay in the cell performance was observed in the several short‐term load tests studied under several H2 S concentration (0–500 ppm) during 1h, and even in 500 ppm H2 S/H2 during 70 h, indicating that this material could be a potential sulfur‐tolerant anode.